Effect of Lower Extrmity Muscle Fatigue on the Kinematic Parameters of Change of Direction Movement in Amateur Football Athletes - Miftah Rahman; Nurlan Kusmaedi; Iwa Ihkwan Hidayat (Journal of Physical Education Health and Sport, 2025)
Muscle fatigue is known to affect movement patterns and increase the risk of knee injury, especially during change of direction (COD) tasks. This study aims to analyze changes in lower-extremity kinematics and physiological responses due to fatigue. The study used a quasi-experimental pre–post design was used to evaluate the effects of induced fatigue on joint mechanics and metabolic responses. A total of ten participants underwent the Functional Agility Short-Term Fatigue Protocol and carried out COD tests before and after fatigue. Lactate levels were measured as an indicator of fatigue, while joint kinematics were assessed using SkillSpector and Kinovea. Results showed a significant increase in lactate levels from 3.02 ± 0.79 mmol/L to 13.78 ± 3.89 mmol/L (p = 0.000), confirming the presence of physiological fatigue. Fatigue induced notable kinematic alterations, including reduced hip abduction and hip adduction, as well as a substantial increase in knee valgus from 14.90 ± 7.549° to 32.60 ± 6.022° (p < 0.001), indicating greater medial knee deviation. In the sagittal plane, increases in hip flexion, knee flexion, and ankle dorsiflexion reflected compensatory postural strategies. Overall, muscle fatigue disrupts movement stability and increases mechanical knee loading, thereby elevating the risk of ACL injury during directional changes.